Islamic Holistic Approach to Ecology: An Examination of Al-Ghazali's Thought in the Context of Contemporary Environmental Ethics - Ahmad Zain Sarnoto (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the ecological dimensions of Al-Ghazali’s thought in Ihya’ Ulum al-Din through a conceptual hermeneutic approach and comparative analysis with contemporary environmental ethics. The objective is to reconstruct the ontological, ethical, and cosmological foundations of Islamic ecology based on the integrated concepts of Tawhid, Khalifah, and Mizan, and to assess their relevance within modern sustainability discourse. This research employs a non-empirical qualitative design relying on classical textual analysis and contemporary environmental literature. The findings indicate that Tawhid establishes an ontological unity of creation, Khalifah constructs a framework of human moral responsibility as trustees of the earth, and Mizan articulates cosmic balance as a normative principle of ecological stability. The integration of these three concepts produces a holistic ecological model that resonates conceptually with planetary boundary theory and sustainability ethics, while remaining grounded in a theocentric metaphysical foundation. The study concludes that Al-Ghazali’s ecological thought is not only historically significant but also theoretically constructive for global environmental ethics. Its main contribution lies in the systematic reconstruction of Islamic ecology as an alternative paradigm in contemporary environmental studies.